ANALISIS BUTIR SOAL SECARA MODERN DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Muhamad Abdul Azis; Mudzakir Chabib (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Item analysis plays a pivotal role in modern educational evaluation, ensuring test items are valid and reliable in measuring student competencies. This paper delves into the methodologies, applications, and benefits of modern item analysis, leveraging advanced technologies like Item Response Theory (IRT), computerized adaptive testing (CAT), and big data analytics. It discusses essential aspects such as difficulty index, discrimination index, and distractor effectiveness, supported by expert opinions and software applications. Additionally, it highlights the challenges in adopting modern analysis methods, such as access to technology, user expertise, and data management issues. The paper concludes that integrating modern item analysis significantly improves the quality of educational assessments.